Vitamin D and pediatric bone health: Important information and considerations for the pediatric orthopaedic surgeon - Fatima Bouftas, BS; Clarabelle DeVries, MD (Elsevier, 2024)
Vitamin D is an essential fat-soluble vitamin produced in the skin during sun exposure. It plays a considerable role in musculoskeletal health and is largely responsible for the regulation of calcium and phosphate metabolism to maintain a healthy, mineralized skeleton. Optimizing bone mineral density in childhood and adolescence is essential to the foundation of skeletal health; however, the literature lacks consensus on values for normal, deficient, and insufficient serum 25-hydroxyvitamin D levels making supplementation and treatment somewhat challenging.The pediatric orthopaedic surgeon is important to optimizing bone health, particularly in the context of bony pathology/injury. Up to 60% of boys and 40% of girls sustain a fracture in childhood. On top of this baseline incidence, children with low vitamin D levels have been noted to be subject to a higher incidence of fractures from normal activities. While the prevalence of vitamin D deficiency in children in the general population has been determined to be 9%, the prevalence of vitamin D deficiency in the pediatric fracture population can be as high as 75% and 61% of the pediatric population has been determined to have vitamin D insufficiency. The pediatric orthopedist also often is the first to diagnose nutritional rickets as these patients can present solely for complaints of limb deformity. Knowledge of appropriate evaluation, vitamin D supplementation, and indications for pediatric endocrinology referral is vital for the treatment of these patients.In the pediatric population, there is a lack of consensus regarding risk factors that warrant screening for vitamin D deficiency, determining insufficient thresholds, and identifying optimal supplementation recommendations and treatment dosages. More research is needed to clarify the ideal amounts of vitamin D necessary through critical growth periods to prevent rickets and to mitigate fracture risk. Regardless, pediatric Orthopaedic surgeons should promote supplementation to all children and treat diagnosed vitamin D deficiency. Key Concepts: (1) Vitamin D plays a vital role in musculoskeletal health and optimizing vitamin D levels in childhood and adolescence is crucial to proper bone development. (2) Vitamin D deficiency and insufficiency in the general population is common; 9% of the pediatric population, representing 7.6 million US children and adolescents, are vitamin D deficient and 61%, representing 50.8 million US children and adolescents, are vitamin D insufficient. The prevalence of vitamin D deficiency in the pediatric fracture population can be as high as 75%. (3) Vitamin D deficiency can lead to nutritional rickets which is the most frequent cause of pediatric bone disease in the world, is entirely preventable, and is characterized by deficient mineralization and subsequent architectural disruption of the physis. (4) Vitamin D supplementation is widely recommended and believed to be beneficial, but there are inconsistent guidelines regarding target levels for optimal vitamin D status.